The role of parallel computing in bioinformatics - Akhurst, Timothy John (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
The need to intelligibly capture, manage and analyse the ever-increasing amount of publicly available genomic data is one of the challenges facing bioinformaticians today. Such analyses are in fact impractical using uniprocessor machines, which has led to an increasing reliance on clusters of commodity-priced computers. An existing network of cheap, commodity PCs was utilised as a single computational resource for parallel computing. The performance of the cluster was investigated using a whole genome-scanning program written in the Java programming language. The TSpaces framework, based on the Linda parallel programming model, was used to parallelise the application. Maximum speedup was achieved at between 30 and 50 processors, depending on the size of the genome being scanned. Together with this, the associated significant reductions in wall-clock time suggest that both parallel computing and Java have a significant role to play in the field of bioinformatics.
Keywords: Bioinformatics; Parallel programming (Computer science); LINDA (Computer system); Java (Computer program language); Parallel processing (Electronic computers); Genomics -- Data processing